2008
DOI: 10.1002/art.23936
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to citrullinated α‐enolase peptide 1 are specific for rheumatoid arthritis and cross‐react with bacterial enolase

Abstract: Objective. To map the antibody response to human citrullinated ␣-enolase, a candidate autoantigen in rheumatoid arthritis (RA), and to examine crossreactivity with bacterial enolase.Methods. Serum samples obtained from patients with RA, disease control subjects, and healthy control subjects were tested by enzyme-linked immunosorbent assay (ELISA) for reactivity with citrullinated ␣-enolase peptides. Antibodies specific for the immunodominant epitope were raised in rabbits or were purified from RA sera. Cross-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
313
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 339 publications
(339 citation statements)
references
References 43 publications
(39 reference statements)
11
313
0
2
Order By: Relevance
“…The results depicted in Table 4 show that although citrullinated fibrinogen and Sa were recognized by IgG ACPAs from more than half of the patients with RA, virtually none of the IgG ACPApositive sera from healthy relatives recognized these antigens. (The results described in Table 4 were obtained with a linear ␣-enolase peptide containing a small difference in sequence compared with the peptide used by Lundberg et al, whose report appears elsewhere in this issue [28]). Interestingly, most of the RA sera that reacted with citrullinated antigens recognized both citrullinated fibrinogen and Sa.…”
Section: Resultsmentioning
confidence: 93%
“…The results depicted in Table 4 show that although citrullinated fibrinogen and Sa were recognized by IgG ACPAs from more than half of the patients with RA, virtually none of the IgG ACPApositive sera from healthy relatives recognized these antigens. (The results described in Table 4 were obtained with a linear ␣-enolase peptide containing a small difference in sequence compared with the peptide used by Lundberg et al, whose report appears elsewhere in this issue [28]). Interestingly, most of the RA sera that reacted with citrullinated antigens recognized both citrullinated fibrinogen and Sa.…”
Section: Resultsmentioning
confidence: 93%
“…Linear citrullinated (Cit) peptides derived from the sequence of human proteins were as follows: PAD 211-30 (VCitVFQATCitGKLSSKCSVVLG) derived from PAD, vim 60-75 (VYATCitSSAVCitLCitSSVP) derived from vimentin, enol [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] (KIHACitEIFDSCitGNPTVE) derived from alpha-enolase, fibrin 617-31 (HSTKCitGHAKSCitPVCitG) derived from the alpha chain of fibrinogen, col-II 358-75 (GACitGLTGCitPGDAGPPGPP) from type II collagen and fillaggrin [SHQEST(Cit)G(Cit)SRGRSGRSG] derived from filaggrin. A non-citrullinated peptide, ctrlPAD (EPLGLQCTFINDFFTYHIRH) derived from PAD was used as control.…”
Section: Synthetic Peptidesmentioning
confidence: 99%
“…Specifically, the vimentin and fibrinogen epitopes are the most frequently recognized by sera from ACPA-positive patients with long-standing RA [17]. Lundberg et al identified an immunodominant epitope in citrullinated alpha-enolase, to which antibodies are specific for RA [18]. Because RA patients recognize diversely distinct citrullinated epitopes of the same parent protein, an approach based on citrullinated peptides rather than whole proteins has been used in an attempt to obtain optimal discrimination ability [19].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, P. gingivalis enolase is cross-reactive with the immunodominant epitope of citrullinated ENO1 in RA patients. [13]…”
Section: Introductionmentioning
confidence: 99%
“…The affinity-purified antibodies to the citrullinated epitope of ENO1 also react with native ENO1 [13]. Antibodies to ENO1 have been reported in a variety of infectious and autoimmune diseases, including RA [14].…”
Section: Introductionmentioning
confidence: 99%